Nicorandil attenuates ventricular dysfunction and organ injury after cardiopulmonary bypass. (1st December 2022) - Peng, Yun-Wen; Major, Terry; Deatrick, Kristopher B.; Mohammed, Azmath; Jeakle, Mark; Charpie, John R.
Abstract: Background: Nicorandil, an adenosine triphosphate-sensitive potassium channel agonist and nitric oxide donor, is a coronary vasodilator used to treat ischemia-induced chest pain, but it's potential cardioprotective benefits during open heart surgery have not been thoroughly investigated. The study objective was to assess the impact of nicorandil on postoperative ventricular dysfunction and end-organ injury in an established experimental model of open-heart surgery with cardiopulmonary bypass (CPB) and cardioplegic arrest. We hypothesized that nicorandil would attenuate myocardial ischemia-reperfusion (IR) injury, preserve ventricular function, and reduce end-organ injury. Methods: Rabbits were cannulated for CPB, followed by 60 min of aortic cross-clamp (ACC) with cold cardioplegic arrest, and 120 min of recovery after ACC removal. Nicorandil (or normal saline vehicle) was given intravenously 5 min before ACC and continued throughout the recovery period. Left ventricular developed pressure (LVDP), systolic contractility (LV + dP/dt), and diastolic relaxation (LV -dP/dt) were continuously recorded, and blood and tissue samples were collected for measurement of oxidant stress (OS), inflammation, apoptosis, and organ injury. Results: Nicorandil significantly attenuated IR-induced LV dysfunction compared to saline control (R-120: LV + dP/dt: 1596 ± 397 vs. 514 ± 269 mmHg/s, p = 0.010; LV -dP/dt: −1524 ± 432 vs. -432 ± 243 mmHg/s, p < 0.001; LVDP: 55 ± 11 vs. 22 ± 5 mmHg, p = 0.046). Furthermore, nicorandil inhibited IR-induced increases in OS, inflammation, apoptosis, and organ injury. Conclusions: Nicorandil exhibits myocardial protection by attenuation of IR-induced LV dysfunction associated with OS, inflammation, apoptosis, and organ injury. Nicorandil should be explored further as a potential therapeutic strategy for limiting global IR injury during open-heart surgery in humans. Highlights: Open-heart surgery requires cardiopulmonary bypass and cardioplegic arrest Cardiopulmonary bypass with cardioplegic arrest is associated with end-organ injury Nicorandil, a coronary vasodilator, may provide protection during cardiac surgery In an experimental CPB model, nicorandil attenuates heart, kidney and brain injury Nicorandil is a potential therapeutic strategy to limit post-bypass organ injury